Fondo Latinoamericano para arroz de riego (FLAR): nueva asociación para el sector arrocero - Zorrilla de San Martín, Gonzalo (International Center for Tropical Agriculture, 2010)
Latin American Fund for Irrigated Rice (FLAR): A new alliance for the rice sector The background, structure, mission, and objectives of the Latin American Fund for Irrigated Rice (FLAR, its Spanish acronym) are briefly described. The Fund, created in 1995, was the result of an initiative of several Latin American rice institutions that decided to join efforts to endorse and grant continuity to the work in rice improvement and development that had been carried out for many years by the International Center for Tropical Agriculture (CIAT). FLAR, currently formed by agricultural institutions of 15 countries of the region, strives to serve its partners in three areas: development of technology to achieve a competitive, profitable, efficient, and environmentally sustainable crop; reduction of unitary production costs to indirectly favor consumers; and strengthening of the national rice sectors of Latin America and the Caribbean.